A multiplexed, automated immuno-matrix assisted laser desorption/ionization mass spectrometry assay for simultaneous and precise quantitation of PTEN and p110α in cell lines and tumor tissues. Issue 21 (29th September 2021) - Froehlich, Bjoern C.; Popp, Robert; Sobsey, Constance A.; Ibrahim, Sahar; LeBlanc, Andre; Mohammed, Yassene; Buchanan, Marguerite; Aguilar-Mahecha, Adriana; Pötz, Oliver; Chen, Michael X.; Spatz, Alan; Basik, Mark; et al.
Abstract : Multiplexed immuno-MALDI-MS based on simultaneous enrichment provides high accuracy and precision for the combined quantitation of PTEN and p110α. Abstract : The PI3-kinase/AKT/mTOR pathway plays a central role in cancer signaling. While p110α is the catalytic α-subunit of PI3-kinase and a major drug target, PTEN is the main negative regulator of the PI3-kinase/AKT/mTOR pathway. PTEN is often down-regulated in cancer, and there are conflicting data on PTEN's role as breast cancer biomarker. PTEN and p110α protein expression in tumors is commonly analyzed by immunohistochemistry, which suffers from poor multiplexing capacity, poor standardization, and antibody crossreactivity, and which provides only semi-quantitative data. Here, we present an automated, and standardized immuno-matrix-assisted laser desorption/ionization mass spectrometry (iMALDI) assay that allows precise and multiplexed quantitation of PTEN and p110α concentrations, without the limitations of immunohistochemistry. Our iMALDI assay only requires a low-cost benchtop MALDI-TOF mass spectrometer, which simplifies clinical translation. We validated our assay's precision and accuracy, with simultaneous enrichment of both target proteins not significantly affecting the precision and accuracy of the quantitation when compared to the PTEN- and p110α-singleplex iMALDI assays (<15% difference). The multiplexed assay's linear range is from 0.6–20 fmol with accuracies of 90–112% for both target proteins, and the assay is free of matrix-related interferences. The inter-day reproducibility over 5-days was high, with an overall CV of 9%. PTEN and p110α protein concentrations can be quantified down to 1.4 fmol and 0.6 fmol per 10 μg of total tumor protein, respectively, in various tumor tissue samples, including fresh-frozen breast tumors and colorectal cancer liver metastases, and patient-derived xenograft (PDX) tumors.